Effect of Ecotype and Latitude on Growth, Frost Hardiness, and Oxidative Stress of South to North Transplanted Scots Pine Seedlings - Erja Taulavuori; Kari Taulavuori; Ahti Niinimaa; Kari Laine (International Journal of Forestry Research)
Ecotypes of Pinus sylvestris seedlings from Kuhmo (64°N) and Ranua (66°N) were transplanted to 0 (control), 1, 2, and 3°N higher latitude in Northern Finland in 1997. Sampling was carried out twice per year (spring/autumn) during 1998–2000. Shoot elongation, total nitrogen concentration, frost hardiness and oxidative stress state (lipid peroxidation, glutathione reductase activity, and protein oxidation) in the needles were analyzed. Comparison between the seasonal sampling times indicated that total nitrogen, lipid peroxidation, glutathione reductase activity, and protein oxidation were lower in autumn, during which the frost hardiness was higher. The above suggests that the stress conditions were higher in spring. Comparison between the origins of the seedlings demonstrated that shoot elongation of the northern origin were minor, while their total nitrogen concentrations and frost hardiness were more pronounced. Effect of latitude on elongation of Scots pine is most probably a result of a combination of temperature and light quality. No delay in frost hardening due to higher latitude was observed during the autumnal equinox. No marked stress caused by transplantation to the north was either observed. It is concluded that southern ecotypes of Scots pine have the potential to adapt to migration driven by a warming climate.